Traditional Chinese medicine foot bath combined with acupoint massage for the treatment of diabetic peripheral neuropathy: A systematic review and meta‐analysis of 31 RCTs. Issue 2 (29th October 2019) - Fu, Qinwei; Yang, Hui; Zhang, Lanzhi; Liu, Yang; Li, Xinrong; Dai, Menglin; Yang, Yepeng; Yang, Shasha; Xie, Yan; Liu, Ying; Fu, Li; Liu, Zhiqing; et al.
Summary: In this study, we aim to evaluate the efficiency and safety of traditional Chinese medicine foot bath combined with acupoint massage for the treatment of diabetic peripheral neuropathy. A total of eight online databases were searched to collect studies published up to February 2019. Study quality of each included article was evaluated by the Cochrane Collaboration risk of bias tool. Systematic reviews and meta‐analyses were conducted based on the Cochrane systematic review method by using the RevMan 5.3 software. Traditional Chinese medicine foot bath combined with acupoint massage was the main therapy in experimental group. Interventions in control groups include western medicine, oral traditional Chinese medicine, other symptomatic treatment of western medicine, and blank control. Primary outcomes in this study include sensory nerve conduction velocity (SNCV), motor nerve conduction velocity (MNCV), total effective rate, and neuropathic syndrome score. Finally, 31 trials involving 3284 participants were included. The results of systematic reviews and meta‐analyses showed that traditional Chinese medicine foot bath combined with acupoint massage was significantly better compared with the control groups in terms of the total effective rate, SNCV, MNCV, and neuropathic syndrome score. No case of adverse effect was reported. These findings show that traditional Chinese medicine foot bath combined with acupoint massage may be safer and more effective for the treatment of DPN. However, due to the low methodological quality, further research with randomized controlled trials (RCTs) of higher quality is required to prove its efficacy and better evidence for clinical treatment.